Database for reverse dives - Sanders, R.; McClymont, D.; Ferrier, B.; Cornelius, M.; Ordeman, D.; George, S.; Vaughan, A. (coachesinfo.com)
Database for Reverse Dives - Obtained from Analysis of Dives at The FINA Diving World Cup, Wellington, 1999. - Data - Typical Postures - How would you or your diver compare?